Derivation of aquatic predicted no-effect concentration (PNEC) for ibuprofen and sulfamethoxazole based on various toxicity endpoints and the associated risks. (February 2018) - Huang, Qiusen; Bu, Qingwei; Zhong, Wenjue; Shi, Kaichong; Cao, Zhiguo; Yu, Gang
Abstract: For pharmaceuticals, the ecological risk assessment based on traditional endpoints of toxicity could not be properly protective in the long run since the mode of action could vary because they are intended for different therapeutic uses. In this study, the predicted no-effect concentrations ( PNEC s) of two selected pharmaceuticals, ibuprofen (IBU) and sulfamethoxazole (SMX), were derived based on either traditional endpoints of survival and growth data or some nonlethal endpoints such as reproduction, biochemical and molecular data. The PNEC s of IBU based on biochemical-cellular and reproduction data were 0.018 and 0.026 μg L −1 that were significantly lower than those derived from other endpoints, while the lowest PNEC for SMX derived from growth data with the concentration of 0.89 μg L −1 . Ecological risk assessment was performed for IBU and SMX to the aquatic environment by applying hazard quotient and probabilistic distribution based quotient ( DBQ s) methods. The results showed that the probability of DBQ s of IBU exceeding 0.1 was 11.2%, while for SMX the probability was 0.9% that could be neglected. Highlights: PNECs of two pharmaceuticals were derived from various toxicity endpoints. The traditional endpoints could not be the most sensitive ones for pharmaceuticals. The most sensitive endpoint varies among pharmaceuticals we test. The probability of risk quotient of ibuprofen exceeding 0.1 was 11.2%.